Science Education and Sustainable Development - Meena, O. P. (SCHOOL SCIENCE, 2017)
Often people think that the problems which pertain to the environmental issues such as climate change, global warming, ozone depletion, different type pollutions, deforestation, biodiversity loss are to be solved by government or scientists of the world. However, we need to realise that these issues are emerging due to the activities and exploitation of natural resources by the human being. Thus each of us is involved in creating or enhancing these problems as part of the problems. The time has come to take necessary measures to save our future. We should understand the reasons and factors that are responsible for these issues. This paper critically analyses the factors causing environmental issues— imbalance, disturbance like climate change, global warming, ozone depletion, different types of pollutions, biodiversity loss, etc.